The word collector - Reynolds, Peter 1961- (Orchard Books, an imprint of Scholastic, Inc., 2018)
Jerome enjoys collecting and using words that he hears, reads, or sees, and then decides to share his collection with others
Keywords: JUVENILE FICTION / Concepts / Words / bisacsh; JUVENILE FICTION / Visionary & Metaphysical / bisacsh; JUVENILE FICTION / Books & Libraries / bisacsh; Vocabulary; Collectors and collecting; Communication; JUVENILE FICTION / Concepts / Words; JUVENILE FICTION / Visionary & Metaphysical; JUVENILE FICTION / Books & Libraries; Sammeln; Wort; Wortschatz; Junge; Teilen; Bilderbuch